Validation of the Personal Attributes Questionnaire-8: Gender Expression and Mental Distress in the German Population in 2006 and 2018 - Ana Nanette Tibubos; Daniëlle Otten; Manfred E. Beutel; Elmar Brähler (Frontiers Media S.A., 2022)
Objectives: Mental health differences between men and women can be attributed to sex or gender. Due to absence of brief assessments, contributions of gender expressions to the mental health gap between men and women have been understudied. The purpose of this study is to develop and validate a short screening measure of gender expression and test its associations with mental distress.Methods: German representative survey data from 2006 (N = 2,507) and 2018 (N = 2,516) were analysed. A short form of the Personality Attributes Questionnaire with 8 items (PAQ-8) was assessed to measure femininity and masculinity. Validity of the PAQ-8 was tested and associations between femininity, masculinity and mental health were examined.Results: PAQ-8 was a valid screening measure to assess gender expression. Compared to 2006, femininity increased in women and decreased in men in 2018. Higher levels of femininity and masculinity were associated with lower distress. Sex was no longer predictive for mental distress when femininity, masculinity, age and equivalised income were considered.Conclusion: Our findings support the use of gender measures, which may be more predictive of mental health than sex.